Zalecenia i zachęty do życia doskonałego w korespondencji Grzegorza z Nazjanzu - Widok, Norbert (Vox Patrum, 2018)
The text of the article is an analysis of Gregory of Nazianzus’ comments on Christian perfection. They were selected from his letters written in his family regions after returning from Constantinople, where he occupied for two years the position in the episcopal capital. It was a period of almost ten years of his life, until his death in 390, in which he contacted many people mainly through letters, because weak health prevented him from traveling frequently. The analysis of the letters showed that the threads containing recommendations, warnings, cautions, and encouragements were numerous in them. They have been divided in three categories of addresses, i.e. clergy and monks, lay people and family members. Depending on the situation, the needs of addressees, their spiritual disabilities, or even their progress on the path to perfect living, Gregory demonstrated the skills of good spiritual help. His sensitivity to human problems, related to everyday life, triggered his concern for their proper evaluation. All human activity was perceived by him in terms of God’s providence and eternal life. He considered the abidance of Christian principles to be the duty of every follower of Jesus Christ, so he had made efforts to ensure that the recipients of his letters were not indifferent to spiritual values.